Effectiveness of a Vestibular Rehabilitation Protocol to Improve the Health-Related Quality of Life and Postural Balance in Patients with Vertigo - Tsukamoto, Heloísa Freiria; Costa, Viviane de Souza Pinho; Silva, Rubens Alexandre da, Junior; Pelosi, Gislaine Garcia; Marchiori, Luciana Lozza de Moraes; Vaz, Cláudia Regina Sanches; Fernandes, Karen Barros Parron (International Archives of Otorhinolaryngology, 2015)
Introduction Dizziness can be characterized as a balance disorder that causes discomfort, leading to several functional limitations. Currently, vestibular rehabilitation has been highlighted as a possible treatment.Objective Analyze the effects of completing a vestibular rehabilitation treatment protocol on quality of life and postural balance in patients with vestibular complaints, as well as to compare these effects between the patients taking or not taking antivertigo drugs.Methods A nonrandomized controlled trial was performed with 20 patients previously diagnosed with vestibular diseases. Information regarding vertigo symptoms, quality of life as assessed through the Dizziness Handicap Inventory, visual analog scale of dizziness, and stabilometry using force platform was collected. Patients were treated for 12 weeks by a custom protocol. The sample was divided into two groups according to the use (medicated group, n = 9) or not (control group, n = 11) of antivertigo drugs.Results There was improvement in quality of life (p < 0.001) and intensity of dizziness (p = 0.003) with the intervention. An improvement of postural balance was observed through functional tests. However, no statistically significant difference was noted in stabilometry. When both groups were compared, no statistically significant differences between the variations of the variables analyzed were found in the re-evaluation session.Conclusion Quality of life and postural balance are improved with intervention. However, this improvement is not associated with pharmacologic treatment.
Keywords: dizziness; rehabilitation; quality of life; postural balance; medicines